CHALLENGES AND OPPORTUNITIES TO COLLABORATIVE DISTANCE LEARNING IN ESP INSTRUCTION - Ridwan, Arfiyan; Athena, Tera (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2023)
In post pandemic instruction fueled by digital media and technology, distance learning emerges as a powerful opportunity for higher education collaboration. The Directorate of Students’ Learning, Ministry of Education and Culture of Indonesia opens opportunities for universities across Indonesia to have collaborative online learning with those students based on underprivileged regions in Indonesia. This research investigates a case of collaborative online learning project between two universities in East Java and East Nusa Tenggara province with two ESP courses designed collaboratively and implemented with shared classes in online mode. Through this case study, two things are explored during the program: challenges and opportunities in the stage of course development and course implementation. Two course developers, four university instructors, and thirteen selected students from both universities were involved in this study. Data collection combined interviews, virtual observations, and instructional documents. Analysis employed thematic layering and triangulation, revealing challenges in four areas: course development, technology readiness, teaching methods, and student support. However, rooms of improvement are there for more prepared future collaboration. Despite the challenges, collaborative distance learning conducted by both universities can be a lesson to learn for a better online instruction in the future amidst the pluralistic backgrounds of the students and problematic technology support.